Recombinant human enterovirus 71 in hand, foot and mouth disease patients - Yoke, Fun Chan; Bakar, Sazaly Abu (Penerbit Universiti Sains Malaysia, 2004)
Hand, foot and mouth disease (HFMD) is a common illness of infants and young children less than 10 years of age. It is characterized by fever, ulcers in the oral cavity, and rashes with blisters that appear on the palm and sole. The most common causal agents of HFMD are coxsackievirus A16 (CV-A16) and human enterovirus 71 (HEV71), but other enteroviruses, including CV-A5 and CV-A10, can also cause it.